1989
DOI: 10.1159/000146793
|View full text |Cite
|
Sign up to set email alerts
|

The Vasculature of Xenotransplanted Human Melanomas and Sarcomas on Nude Mice

Abstract: The tumor-inherent vasculature plays a major role with respect to tumor sensitivity to ionizing radiation. Ultrastructural studies of the tumor vasculature are necessary in order to obtain more detailed information on the architecture and structure and on the sites affected by tumor therapy. The vasculature of xenotransplanted human tumors on nude mice was investigated in this study by means of scanning and transmission electron microscopy. Structurally complete real arteries or veins are neither to be seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Areas of high vessel density observed within RIP1‐Tag5 tumors may represent foci of active angiogenesis. The appearance of vascular sinusoids and lacunes in solid tumors has also been described for melanomas and was correlated with areas of maximal interstitial pressure 34. The aberrant vascular features that we describe for the spontaneously arising solid tumors in RIP1‐Tag5 mice are similar to intravital microscopy studies performed on experimental pancreatic cancer in the rat 35.…”
Section: Discussionsupporting
confidence: 78%
“…Areas of high vessel density observed within RIP1‐Tag5 tumors may represent foci of active angiogenesis. The appearance of vascular sinusoids and lacunes in solid tumors has also been described for melanomas and was correlated with areas of maximal interstitial pressure 34. The aberrant vascular features that we describe for the spontaneously arising solid tumors in RIP1‐Tag5 mice are similar to intravital microscopy studies performed on experimental pancreatic cancer in the rat 35.…”
Section: Discussionsupporting
confidence: 78%
“…Timar & Toth (54) described sinusoids in melanomas lined by tumor cells and cited literature supporting the existence of such channels in breast cancer. In 1989, Konerding et al (55, 56) reported morphological descriptions of non‐endothelial cell‐lined “vessels” in animal models of melanoma and observed that thin branches of tumor cells morphologically resembled endothelial cells. Konnerding et al (56) therefore speculated that tumor cells may form vessels, although expressing uncertainty about the extent to which these channels provided perfusion to the tumor.…”
Section: Vasculogenic Mimicry Of the Tubular Typementioning
confidence: 99%
“…There is strong evidence suggesting that human cytotrophoblasts adopt an endothelial cell phenotype as they actively participate in the dynamics of establishing the placenta and primordial microcirculation, which has been designated 'trophoblast pseudo-vasculogenesis' [9,10,11]. With respect to tumor vascularization, the possibility of the formation or lining of a microcirculation by tumor cells has been suggested by several studies, on the basis of morphologic analyses and numerous pathology reports [12,13,14,15,16,17,18,19,20,21,22,23,24,25]. In a recent review by Tímár and Tóth [26], the diagnostic and clinical significance with regard to human melanoma and breast cancer tumor cell-lined sinuses and vascular channels was presented.…”
Section: Molecular Vasculogenic Mimicry By Aggressive Tumor Cellsmentioning
confidence: 99%